2022
DOI: 10.1155/2022/1346543
|View full text |Cite|
|
Sign up to set email alerts
|

Research on Open Oral English Scoring System Based on Neural Network

Abstract: This study designs and implements a scoring system for open-spoken English using NN technology. The system scores the oral recording from the phonetic level and the text level, respectively, and can comprehensively evaluate its oral level. The system will separately score the spoken speech and the spoken content through different scoring models and add the scoring results as the final score, in which the spoken content is obtained by text transcription of the recording by an external speech recognition engine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Xin Wang et al [10] designed and implemented a scoring algorithm for open-spoken English using the improved neural network (NN) approach. This algorithm evaluates the oral recording from both phonetic and text levels.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Xin Wang et al [10] designed and implemented a scoring algorithm for open-spoken English using the improved neural network (NN) approach. This algorithm evaluates the oral recording from both phonetic and text levels.…”
Section: Related Workmentioning
confidence: 99%
“…For each iteration, the FA technique refines and updates the parameter values using the random movement updation of fireflies, which is represented in Eqn. (10).…”
Section: Adaptive Scoring Algorithmmentioning
confidence: 99%
“…Offline, users may see a report detailing their performance across many modalities. Wang(37) uses NN technology to score open-spoken English. The system evaluates the oral recording's phonetic and text levels and oral level.…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%